Deactivation and regeneration of Pt‐modified zeolite Beta–Bindzil extrudates in n‐hexane hydroisomerization. Issue 6 (19th February 2021) - Vajglová, Zuzana; Kumar, Narendra; Peurla, Markus; Hupa, Leena; Semikin, Kirill; Sladkovskiy, Dmitry A; Murzin, Dmitry Yu
Abstract: BACKGROUND: The metal–acid bifunctional catalysts are widely used in many industrially significant chemical processes, including hydroisomerization of n ‐hexane. Deactivation and regeneration of metal–acid bifunctional extrudates was investigated in continuous n ‐hexane hydroisomerization in a fixed‐bed reactor. Four Pt/H‐Beta‐25 catalysts containing 30% Bindzil binder were prepared with the same composition and controlled metal deposition. RESULTS: Different preparation steps led to differences in the mechanical strength, Pt particle size, acidity and strength, metal‐to‐acid site ( c Pt / c AS ) ratio and proximity between two types of active sites. A very slow deactivation and high selectivity to C6 isomers was obtained when Pt was deposited on H‐Beta‐25 zeolite. CONCLUSION: Initial selectivity to the desired products was correlated with the physicochemical properties of the catalysts. Location of the metal has a larger influence on catalyst deactivation of the bifunctional catalysts rather than the metal‐to‐acid site ratio or site proximity. Decline of n ‐hexane conversion and selectivity to C6 isomers were correlated with changes in the textural properties and acidity of the deactivated catalyst, respectively. © 2021 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.